KEBIJAKAN KEPALA SEKOLAH DALAM PEMENUHAN KEWAJIBAN GURU MENGAJAR 24 JAM - Yesi Septriani Yesi Septriani (Manajer Pendididikan, 2017)
The purpose of this research are: (1) the material of principal policy, (2) implementationof principal policy, and (3) the effect of principal policy. The method of this research is usingdescriptive qualitative with observation technique, interview, and documentation. The subject ofthis research is principal, vice of principal, operator, and teacher. The policy of principal ismaximizing the portion 24 hours face to face classroom and giving alternalive for teacher thatshortage in teaching hour. The result of the research shows that is not fulfilled teacher obligationteaching 24 hours at SMPN 20 Seluma for all teachers yet.